(a-b)(a+b)-(a-c)(a+c)-(c-b)(c+b)=0 (доказать тождество)

(a-b)(a+b)-(a-c)(a+c)-(c-b)(c+b)=0 (доказать тождество)
Гость
Ответ(ы) на вопрос:
Гость
(a-b)(a+b)-(a-c)(a+c)-(c-b)(c+b)=0 a^2+ab-ab-b^2-(a^2+ac-ac-c^2)-(c^2+cb-cb-b^2)=0 a^2-b^2-a^2+c^2-c^2+b^2=0 -b^2+c^2-c^2+b^2=0 c^2-c^2=0 0=0
Гость
(a-b)(a+b)-(a-c)(a+c)-(c-b)(c+b)=0 a^2-b^2-a^2+c^2-(c-b)*(c+b)=0 -b^2+c^2-(c-b)*(c+b)=0 -b^2+c^2-(c^2-b^2)=0 -b^2+c^2-c^2+b^2=0 -b^2+b^2=0 0=0 Тождество доказано! 
Не нашли ответ?
Ответить на вопрос
Похожие вопросы